Determinants of intention to use FinTechs services by accounting students: a mixed methods approach - Anderson Betti Frare; Carla Milena Gonçalves Fernandes; Mariele Castro dos Santos; Alexandre Costa Quintana (BBR: Brazilian Business Review)
Fintechs are startups that operate in the financial sector and have gradually been receiving space in the market. However, it is still not clear which elements lead individuals, especially those involved in the business field, to adopt and use these services. Thus, this study aims to analyze which elements encourage the behavioral intention to use Fintech services from the perspective of students in the business field. The theoretical basis and hypothesis development were based on the Unified Theory of Acceptance and Use of Technology (UTAUT), which contemplates the facilitating conditions, performance expectancy, effort expectancy, social influence, and the behavioral intention to use said services. The study also included the variable “security” as an antecedent. Age and gender were controlled for this study. A survey resulted in a sample of 107 students, and the data was analyzed with a mixed-method approach: partial least squares - structural equation modeling (PLS-SEM) and fuzzy-set qualitative comparative analysis (fsQCA). With PLS-SEM, the findings demonstrate the positive effect of performance expectancy, effort expectancy and security on the behavioral intention to use fintech services. The fsQCA showed that different causal configurations can lead students to a high adoption of services provided by these startups. This study brings up new evidence that contributes to the UTAUT theory by intertwining this discussion with the security variable perceived during technology usage. Furthermore, it expands the entire discussion to the context of accepting a contemporary technology. Regarding the students, practical evidence is gathered regarding the determinants of their intention to use financial services.